ATTITUDE DES ENSEIGNANTS DE L’ECOLE PRIMAIRE SAINT JOSEPH FACE AUX ENFANTS DU CENTRE SAINT LAURENT - , Michel KAYOMBA N’SINGOMA (IJRDO - Journal of Social Science and Humanities Research, 2019)
They are numerous among the children of the streets those that didn't frequent the school, or abandoned it too early. The school is not only inaccessible because of the direct economic costs (enrollments) and indirect (uniforms, displacements, etc.), but it is also in the inability to answer the needs of the children. The abandonment of the school is a crucial factor that drags the child to discover the life of the street and all dangers that are bound him.In its mission of socialization, the Center Saint Laurent for framing of the children family breaking proceeds by school recuperation, enrolling these children in public schools. In these schools, these children are so much the object of the prejudices on behalf of the teachers that of their colleagues who qualify them, nickname them of the thieving children, of the children accused of the sorcery, of the recovered children, stubborer, impolite, that like brutal games… These children are punished severely by their teachers and other authorities of the school, the interior regulation of the school is observed scrupulously to their consideration.This article shows the attitudes that the teachers of the school Saint Joseph and other pupils display facing the children in family breaking sheltered to the Center Saint Laurent. This analysis shows that it is important that the teacher considers all pupils as learners confided to him in order to transmit the knowledge; to have some prejudices towards pupil's category would reduce his role of educator and risk to cause the school dwindle.